2020
DOI: 10.1109/access.2020.3005536
|View full text |Cite
|
Sign up to set email alerts
|

Solution for Information Overload Using Faceted Search–A Review

Abstract: In the modern society, Internet provides massive amounts of heterogeneous information, hence Information overload has become an ubiquitous issue. In this paper, we conduct a large scale quantitative study for articles dealing with (1) information overloading; (2) faceted search; and (3) filtering the data in three major databases, namely, Web of Science, ScienceDirect, and IEEE Explore. These three databases have presented 172 articles, which can be classified into four categories. The first category contains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 165 publications
0
12
0
Order By: Relevance
“…They also predicted the direction of advancements in the ES area depending on the social state of information search. The authors of [9,[33][34][35][36] studied the development of new decision support tools and explored the visual knowledge system. The main contribution of these studies was to find out how a system can achieve the intended enhancement based on the survey that was performed on the projects by using meta requirements.…”
Section: Survey and Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…They also predicted the direction of advancements in the ES area depending on the social state of information search. The authors of [9,[33][34][35][36] studied the development of new decision support tools and explored the visual knowledge system. The main contribution of these studies was to find out how a system can achieve the intended enhancement based on the survey that was performed on the projects by using meta requirements.…”
Section: Survey and Reviewmentioning
confidence: 99%
“…The main challenges in adopting FS are classified according to their nature, presented in this section, and citations for further discussion are given. Although smart FS offers numerous benefits, the evaluation metrics demonstrate that these technologies are limited by information overload [9]. The surveyed works indicated that researchers are concerned about the challenges associated with information filtering and its use.…”
Section: Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, in order to achieve an efficient mechanism, three main elements should be considered and carefully designed, namely; information retrieval, information processing, and information presentation (Figure 1). All these three elements should be integrated in order to have a fully functional search engine [1], [2]. The first two elements have been covered in our previous publications [3].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, faceted search Mahdi et al. ( 2020 ) allows narrowing results by certain aspects, by providing the distribution of values of certain attributes across the entire result set. In addition to presenting these distributions, the user can limit attributes to specific values, thus reducing the result set to only results that match all selected values Ben-Yitzhak et al.…”
Section: Introductionmentioning
confidence: 99%